The Effect of Product Development and Product Quality Control on Sales Volume of Yakult Products in Indarung District, Padang City - Putra, Sapta Eka; Rahmawati, Widya; Savira, Anggun (Lembaga Riset dan Inovasi Al-Matani, 2022)
This study aims to determine and analyze how much influence product development and product quality control have on sales volume at PT Yakult in Indarung District, Padang City. Descriptive quantitative research method with a sample of 100 respondents using purposive sampling technique. The instruments used in the study were questionnaires and data analysis techniques using multiple linear regression, t test, F test and coefficient of determination. Based on multiple linear analysis obtained Y = 12.785 + 0.319 + 0.192 X2 + e. Based on the t test analysis, it is found that product development (X1) has a positive and significant effect on the sales volume of yakult products in Indarung District, Padang City, then product quality control (X2) has a positive and significant effect on the sales volume of these products. The results of the F test prove that, product development and product quality control together have a positive and significant effect on consumer sales volume on yakult products in Indarung District, Padang City. The coefficient of determination test results get an Adjusted R-Square value of 60.6% and the remaining 39.4% which is explained by other variables such as price, marketing strategy, distribution, service.